Vorgehensweisen mathematisch potenziell begabter Dritt- und Viertklässler beim Problemlösen: Empirische Untersuchungen zur Typisierung spezifischer Problemlösestile (mathematica didactica, 2013)
Starting from a complex interdisciplinary approach this study uses established theoretical modelling of mathematical aptitude development in primary school age; conceptional- analytical structuring approach to (mathematical) problem solving and a theoretical position based on empirical constructions gained from the classification of specific mathematical problem solving styles of potentially gifted third and fourth form primary school children.